Health Promotion through a Digital Peer Education Platform for Teenage Pregnancy to Reduce Stunting - Sri Rahma Friani; Meyana Marbun; Deswidya S Hutauruk; Elsida Aritonang (Information Technology and Science (ITScience), 2026)
Adolescents who experience early pregnancy before the age of 18–20 years are at greater risk of giving birth to low-birth-weight babies and experience limited ability to maintain ideal nutritional care. National data shows that the prevalence of stunting in Indonesia, according to local studies, shows that children born to adolescent mothers have a risk of stunting of up to 44.4%, much higher than children of adult mothers. Peer education plays a role in the delivery of information carried out by peers who are considered more trustworthy and easier to accept. Health promotion interventions that use digital platforms are easily accessible; the digital media arena allows for the dissemination of information quickly, interestingly, and according to adolescent learning styles. The purpose of this study was to determine the influence of the Digital Peer Education Platform on adolescent pregnancy knowledge to reduce stunting. This study used a quasi-experimental design, using a pre-test-post-test control group design. Two groups were randomly selected and then given a pre-test to determine whether there were any differences between the experimental and control groups. Data analysis included paired t-tests and independent t-tests to determine differences in knowledge and attitude scores. The results of this study, based on the analysis of the Paired Sample T-Test, indicate that peer education has an effect on adolescents' knowledge levels with a p-value of 0.001 (p<0.05). Suggestions are expected for schools to implement peer education methods in future learning curricula.